PENGARUH EMOTIONAL QUOTIENT (EQ) DAN IKLIM ORGANISASI PADA KEPUASAN KERJA KARYAWAN PADA PT SINAR CIPTA KREASI MEDAN - MEGA SANJAYA; ESTER MANDROFA (JURNAL ILMIAH SIMANTEK, 2020)
PT Sinar Cipta Kreasi Medan is a moving company in the field of firefighting, where the company is experiencing obstacles from some of its employees who do not have emotional intelligence (EQ), where there are still conflicts, both interdepartments within the organization and also outside the organization especially to suppliers and consumers, so it affects the organizational climate that is not very conducive in the company, thus contributing to a decrease in the performance and productivity of the company's work in providing firefighting products, thus lowering the job satisfaction of other employees. As a result this company does not always have good performance and can always complain from the supplier as well as from the customer. This study aimed to find out whether the emotional intelligence (EQ) of the employee and the organizational climate are both partially and one-sidedly and have a positive and significant impact on the employee's work satisfaction with his work at PT Sinar Cipta Kreasi Medan. The analysis of the data on this study used validity and reliability tests, double linear regression analysis and hypothetical tests, where the population in this study was an employee of PT Sinar Cipta Kreasi Medan of 250 people, whereas the method of withdrawal of samples in this study used simple random sampling calculated using the slovin formula which in the end the number of successful samples was drawn by 42 people. The results of this study state that in a superficial and partial sense of emotional intelligence (EQ) and organizational climate have a positive and significant influence on the variable in the employee's job satisfaction with his work at PT Sinar Cipta Kreasi Medan.